LncRNA RP11-59J16.2 aggravates apoptosis and increases tau phosphorylation by targeting MCM2 in AD - Guan, Fulin; Gao, Qichang; Dai, Xinghua; Li, Lei; Bao, Rui; Gu, Jiaao (Frontiers in Genetics, 2022)
Alzheimer’s disease (AD) is a degenerative disease of central nervous system with unclear pathogenesis, accounting for 60%–70% of dementia cases. Long noncoding RNAs (LncRNAs) play an important function in the development of AD. This study aims to explore the role of differentially expressed lncRNAs in AD patients’ serum in the pathogenesis of AD. Microarray analysis was performed in the serum of AD patients and healthy controls to establish lncRNAs and mRNAs expression profiles. GO analysis and KEGG pathway analysis revealed that G1/S transition of mitotic cell cycle might be involved in the development of AD. The result showed that RP11-59J16.2 was up-regulated and MCM2 was down-regulated in serum of AD patients. SH-SY5Y cells were treated with Aβ 1–42 to establish AD cell model. Dual luciferase reporter gene analysis verified that RP11-59J16.2 could directly interact with 3′UTR of MCM2 and further regulate the expression of MCM2. Inhibition of RP11-59J16.2 or overexpression of MCM2, CCK-8 assay and Annexin V FITC/PI apoptosis assay kit results showed that RP11-59J16.2 could reduce cell viability, aggravate apoptosis and increase Tau phosphorylation in AD cell model by inhibiting MCM2. In short, our study revealed a novel lncRNA RP11-59J16.2 that could promote neuronal apoptosis and increase Tau phosphorylation by regulating MCM2 in AD model, and indicated that lncRNA RP11-59J16.2 might be a potential target molecule for AD development.